Knowledge and civil society - Glückler, Johannes; Meyer, Heinz-Dieter; Kaeding-Suarsana, Laura (Knowledge and space, 2022)
Chapter 1. The Place of Civil Society in the Making of Knowledge -- Part I: (Re-)Thinking Civil Society -- Chapter 2. The Dialectic of Civil and Uncivil Society—Fragility, Fault Lines, and Countervailing Forces.-Chapter 3. Civil Society as an Agent of Change -- Chapter 4. Undone Science and Smart Cities: Civil Society Perspectives on Risk and Emerging Technologies -- Part II: Analyzing Civil Society Organizations -- Chapter 5. Specialists for Crumble Cakes? The German LandFrauen Organizations in Social Innovation and as Educational, Social, and Political Institutions -- Chapter 6. Schools of Democracy? Giving Circles and the Civic and Political Participation of Collaborative Philanthropists -- Chapter 7. Time Banks as Transient Civic Organizations? Exploring the Dynamics of Decline -- Part III: Spaces, Networks and Fields -- Chapter 8. Civil Society as Networks of Issues and Associations: The Case of Food -- Chapter 9. The Geography of Giving in the Philanthropic Field -- Chapter 10. Global Authenticity, Local Authority: Epistemic Power, Discursive Geographies, and the Creation of Civil Society Knowledge Networks -- Part IV: Doing Civil Society -- Chapter 11. Democracy Movement and Alternative Knowledge in Hong Kong -- Chapter 12. Epistemic Activism in the United States: Examining Meetings Across the Silos of Civil Society -- Chapter 13. Seeding a New World: Lessons From the #FeesMustFall Movement for the Advancement of Social Justice -- Chapter 14. Civility, Education, and the Embodied Mind—Three Approaches to a New Sentimental Education.
Open Access
Keywords: Aufsatzsammlung; Zivilgesellschaft; Politische Bewegung; Politisches Denken